THE INFLUENCE OF SELF-EFFICIENCY AND KNOWLEDGE OF BUSINESS FINANCIAL MANAGEMENT ON ENTREPRENEURSHIP INTENTION - Tri Nur Hidayah (Program Studi Akuntansi Universitas Kristen Indonesia Paulus, 2023)
The concept of entrepreneurial intention continues to be the focus of research in the field of entrepreneurship, because high entrepreneurial intention can be a driving force to produce more entrepreneurs who have the potential to create jobs, innovation and economic growth. Therefore, an understanding of entrepreneurial intentions is important in efforts to develop and support a sustainable entrepreneurial ecosystem. This paper aims to analyze the influence of self-efficacy and levels of knowledge management finance business to intention entrepreneurship on student Hasanuddin University, force year 2020 And 2021. Respondents totaling 100 students, Which determined use technique purposive sampling . Analysis data performed using multiple linear regression method. The analysis results prove that efficacy self influential significant to intention entrepreneurship. Whereas, level knowledge management finance business No influential to intention entrepreneurship.